Regulating Thermogalvanic Effect and Mechanical Robustness via Redox Ions for Flexible Quasi-Solid-State Thermocells - Peng, Peng; Zhou, Jiaqian; Liang, Lirong; Huang, Xuan; Lv, Haicai; Liu, Zhuoxin; Chen, Guangming (Nano-Micro Letters, 2022)
The design of power supply systems for wearable applications requires both flexibility and durability. Thermoelectrochemical cells (TECs) with large Seebeck coefficient can efficiently convert low-grade heat into electricity, thus having attracted considerable attention in recent years. Utilizing hydrogel electrolyte essentially addresses the electrolyte leakage and complicated packaging issues existing in conventional liquid-based TECs, which well satisfies the need for flexibility. Whereas, the concern of mechanical robustness to ensure stable energy output remains yet to be addressed. Herein, a flexible quasi-solid-state TEC is proposed based on the rational design of a hydrogel electrolyte, of which the thermogalvanic effect and mechanical robustness are simultaneously regulated via the multivalent ions of a redox couple. The introduced redox ions not only endow the hydrogel with excellent heat-to-electricity conversion capability, but also act as ionic crosslinks to afford a dual-crosslinked structure, resulting in reversible bonds for effective energy dissipation. The optimized TEC exhibits a high Seebeck coefficient of 1.43 mV K−1 and a significantly improved fracture toughness of 3555 J m−2, thereby can maintain a stable thermoelectrochemical performance against various harsh mechanical stimuli. This study reveals the high potential of the quasi-solid-state TEC as a flexible and durable energy supply system for wearable applications. Highlights: 1 A redox couple is employed to fulfill the dual-function of both heat-to-electricity conversion and ionic crosslinking. 2 High thermoelectrochemical performance can be achieved at optimized redox concentration, and dual-crosslinked network ensures remarkable mechanical flexibility and robustness. 3 The hydrogel-based quasi-solid-state thermocell can provide stable energy output under harsh mechanical stress and deformations.